2019
DOI: 10.3904/kjim.2017.293
|View full text |Cite
|
Sign up to set email alerts
|

Seropositive rate of the anti-hepatitis A immunoglobulin G antibody in maintenance hemodialysis subjects from two hospitals in Korea

Abstract: The seropositive rate of the anti-HAV antibody in hemodialysis subjects was 95%, which is similar to findings in the general population. Active immunization against hepatitis A is strongly recommended for hemodialysis subjects under 40 years of age after anti-HAV testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…People born after 1980, when the environment was cleaner and the HAV vaccine was yet developed, have been reported to be more susceptible to HAV (25,26). Other similar studies on the seroprevalence of HAV antibodies have been reported steadily over time (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 53%
“…People born after 1980, when the environment was cleaner and the HAV vaccine was yet developed, have been reported to be more susceptible to HAV (25,26). Other similar studies on the seroprevalence of HAV antibodies have been reported steadily over time (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 53%
“…[7] This phenomenon is associated with low seroprevalence of anti-HAV IgG in a specific age group. [8,9] To prevent hepatitis A infection in South Korea, national vaccination programs have been implemented in the military since 2012 and in toddlers since 2015. [10,11] However, there are insufficient preventive measures for people in their 20s, 30s, and 40s, and they are the main age group for recent outbreaks.…”
Section: Dhl and Ws Contributed Equally To This Articlementioning
confidence: 99%
“…[7] This phenomenon is associated with low seroprevalence of anti-HAV IgG in a specific age group. [8,9]…”
Section: Introductionmentioning
confidence: 99%